2016
DOI: 10.1002/mrm.26197
|View full text |Cite
|
Sign up to set email alerts
|

Robust diffusion tensor imaging by spatiotemporal encoding: Principles and in vivo demonstrations

Abstract: Purpose-Evaluate the usefulness of single-shot and interleaved spatiotemporally-encoded (SPEN) methods to perform diffusion tensor imaging (DTI) under various pre-clinical and clinical settings.Methods-A formalism for analyzing SPEN DTI data is presented, tailored to account for the spatially-dependent b-matrix weightings introduced by the sequence's use of swept pulses acting while in the presence of field gradients.Results-With its b-matrix calculations suitably accounted for, SPEN's ability to deliver faith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…SPEN is a single‐shot imaging modality that can also be extended to multishot interleaved operation with certain benefits in the ensuing spatial resolution and sensitivity. SPEN relies on performing a consecutive excitation or refocusing of the spins, achieved by applying a linearly chirped radio frequency (RF) pulse acting in the presence of an encoding gradient G e . In the multislice, fully refocused pulse sequence here assayed (Figure ), spins are first excited by a slice‐selective 90° pulse and then acted upon by a swept 180° inversion pulse, linearly chirping over a bandwidth BW during a time T e while in the presence of a y ‐axis G e gradient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPEN is a single‐shot imaging modality that can also be extended to multishot interleaved operation with certain benefits in the ensuing spatial resolution and sensitivity. SPEN relies on performing a consecutive excitation or refocusing of the spins, achieved by applying a linearly chirped radio frequency (RF) pulse acting in the presence of an encoding gradient G e . In the multislice, fully refocused pulse sequence here assayed (Figure ), spins are first excited by a slice‐selective 90° pulse and then acted upon by a swept 180° inversion pulse, linearly chirping over a bandwidth BW during a time T e while in the presence of a y ‐axis G e gradient.…”
Section: Methodsmentioning
confidence: 99%
“…Additional resolution improvements can result from SPEN’s built‐in ability to restrict the targeted FOVs. Single‐shot studies incorporating SPEN into diffusion schemes have shown this method’s potential for overcoming SE EPI’s characteristic limitations in animals and humans . The purpose of the study is to explore SPEN’s ability to deliver quantitative diffusion breast maps at sub‐millimeter in‐plane resolutions, in clinically relevant situations.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Spatiotemporal encoding (SPEN) approaches, which overcome field distortions thanks to their reliance on stronger imaging gradients and enhanced T 2 * refocusing abilities, 25,26 have also been explored for these aims. SPEN's robustness has been demonstrated in DWI analyses of challenging regions for both animals [27][28][29] and humans, 30,31 including abdominal studies of small pregnant rodents. 27 Still, even these procedures were constrained by the limited sensitivities they could achieve in a single shot, which defined in turn the maximal resolution of the features that could be imaged.…”
mentioning
confidence: 99%
“…Indeed, the resolution inferiority of diffusion breast MRI as compared to DCE is well known . Several alternative pulse sequence strategies were reported with the aim of overcoming this limitation, although they were not available for use in this work. DCIS and other nonmass lesions are also potential challenges for diffusion‐based breast MRI.…”
Section: Discussionmentioning
confidence: 99%